2014
DOI: 10.1073/pnas.1411333111
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious discrimination of social cues from eye whites in infants

Abstract: Human eyes serve two key functions in face-to-face social interactions: they provide cues about a person's emotional state and attentional focus (gaze direction). Both functions critically rely on the morphologically unique human sclera and have been shown to operate even in the absence of conscious awareness in adults. However, it is not known whether the ability to respond to social cues from scleral information without conscious awareness exists early in human ontogeny and can therefore be considered a foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 76 publications
2
46
1
Order By: Relevance
“…Therefore, selective enhanced attention to fearful eyes as seen in our infant data may reflect infants' approach and empathic concern for others in distress (experiencing fear) (73). Alternatively, infants may also look longer at fearful eyes because they expect gaze cues that help them identify the source of threat (74) or because they exhibit a heightened perceptual sensitivity to the large eye whites characteristic of fearful eyes (9). Regardless of the exact nature of this effect, the current findings provide evidence for the notion that infants of this age show a robust fear bias.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, selective enhanced attention to fearful eyes as seen in our infant data may reflect infants' approach and empathic concern for others in distress (experiencing fear) (73). Alternatively, infants may also look longer at fearful eyes because they expect gaze cues that help them identify the source of threat (74) or because they exhibit a heightened perceptual sensitivity to the large eye whites characteristic of fearful eyes (9). Regardless of the exact nature of this effect, the current findings provide evidence for the notion that infants of this age show a robust fear bias.…”
Section: Discussionmentioning
confidence: 86%
“…Prior work with adults demonstrates that emotion perception and, in particular, fear detection (eyes wide open) rely heavily on information from the eye region and occur even in the absence of conscious perception (5)(6)(7)(8).The importance of eye cues for emotion perception has recently been studied in infants. In an event-related brain potential (ERP) study, 7-mo-old infants were found to discriminate between fear and happiness on the basis of eye cues alone (9). Similar to adults, 7-mo-old infants discriminated between emotional eyes without consciously perceiving them (see ref.…”
mentioning
confidence: 99%
“…Corroborating analysis using a cluster-based permutation approach. While the electrode and time window selection for this analysis had not been data derived but followed standards set by previous studies (Jessen & Grossmann, 2014, we aimed to corroborate this main result by a more data-driven search for potential effects using a cluster-based permutation test (Figure 3). In both, the No odor group and the Stranger odor group, nearly identical clusters indicating a significantly response enhancement to fearful (compared to happy) faces was found (No odor: p = .006, Tsum = 3063.8; Stranger odor: p = .021, Tsum = 1272.8).…”
Section: Influence Of Maternal Odor On the Nc Response As Predictedmentioning
confidence: 97%
“…These effects are observed even when the level of awareness or attention is restricted (Mogg and Bradley, 1999; Ohman et al , 2001). In order to investigate this automaticity, numerous laboratories have used the backward masking paradigm (Morris et al , 1998; Whalen et al , 1998; Etkin et al , 2004; Armony et al , 2005; Pessoa et al , 2006; Williams et al , 2006; Ohman et al , 2007; Jessen and Grossman, 2014; Kanat et al , 2015). In a typical backward masking experiment using emotional facial expressions, a target stimulus (e.g., a fearful face) is presented briefly, then immediately replaced by a mask stimulus (e.g.…”
Section: Introductionmentioning
confidence: 99%